Land reforms and changeing agrarian relations - "Damle, C. B." (New Delhi, 1993)
The present study of the impact of land reform legislations on agrarian structure and relations is a notable contribution to land reform studies in India. It focuses on the analysis of agrarian changes in Dakshina Kannada district in the background of agrarian trends in the State of Karnataka as a whole. The study has been further strengthened by investigations of agrarian changes in the two villages, each in the commercial as well as subsistence settings in the district under study.
Keywords: Land reforms